Green in-situ thermal activation ion ink as well as preparation method and application thereof

By mixing the precursor and reducing solvent at room temperature to prepare green in situ thermally activated ionic ink, the problems of pollution, toxicity and complex processes in the preparation of existing conductive inks are solved, and environmentally friendly, simplified processes and efficient conductive ink preparation are achieved.

CN119799075APending Publication Date: 2025-04-11GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510001832.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the preparation process of existing conductive inks, there are problems such as high pollution, high toxicity, complex production process, and pollution to the environment by waste liquid emissions, and the preparation cycle is long and the cost is high.

Method used

The preparation method of green in situ thermally activated ion ink is adopted, and the process flow is simplified by mixing the precursor and the reducing first solvent at room temperature, the preparation of micron/nano metal particles and the introduction of resin or cellulose are avoided.

Benefits of technology

The preparation of environmentally friendly conductive ink is realized, which reduces pollution and toxicity, shortens the preparation time, reduces production costs, and generates conductive metal particles during the sintering process to form a conductive film with excellent conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799075A_ABST
    Figure CN119799075A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electronic materials, and particularly relates to green in-situ thermal activation ion ink as well as a preparation method and application thereof. A preparation method of green in-situ thermal activation ion ink comprises the following steps that 1, precursors are ground, and the precursors are non-metal elementary substance copper-containing precursors, silver-containing precursors, nickel-containing precursors, cobalt-containing precursors or / and gold-containing precursors; and 2, the ground precursor and a first solvent are mixed to prepare the in-situ thermal activation ion ink, the first solvent is a reducing solvent, and the first solvent does not react with the precursor at normal temperature. According to the preparation method, the ink can be prepared through mixing at normal temperature, preparation of micron / nano metal particles is not needed, introduction of resin or cellulose or cellulose derivatives in conventional ink preparation is not needed, organic matter impurities which are difficult to remove at high temperature are avoided, the preparation time is greatly shortened, and the preparation method is more convenient and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic materials, and in particular relates to a green in-situ thermally activated ion ink and a preparation method and application thereof. Background Art

[0002] At present, the preparation process of conductive ink has defects such as high pollution and toxicity of the reagents used, complex production process, and waste liquid discharge will pollute the environment. Therefore, developing environmentally friendly conductive inks and simplifying the preparation process are the prerequisites for the sustainable and healthy development of the printed electronics industry.

[0003] The prior art method for preparing micron / nano metal particle conductive ink has two steps: (1) preparing micron / nano metal particles by physical or chemical methods, removing excess impurities in subsequent purification, and then drying and storing for future use; (2) dispersing the prepared micron / nano metal particles into a solvent and an additive, and mixing them evenly to obtain a conductive ink.

[0004] In the above method, micron / nano metal particles need to be prepared first, then purified and dried, and finally configured into conductive ink. The steps are complicated, the preparation cycle is long, and the production cost is high. Summary of the invention

[0005] The first purpose of the present invention is to propose a method for preparing a green in-situ thermally activated ion ink, which can be prepared by mixing at room temperature, without the need to prepare micron / nano metal particles, and without the need to introduce resins, cellulose or cellulose derivatives used in conventional ink preparation, thereby avoiding organic impurities that are difficult to remove at high temperatures and greatly shortening the preparation time, making it more convenient and efficient.

[0006] The second purpose of the present invention is to provide the above-mentioned preparation method to obtain green in-situ thermally activated ion ink, which is an environmentally friendly conductive ink with no pollution and no toxicity.

[0007] The third purpose of the present invention is to propose the application of the above-mentioned green in-situ thermally activated ion ink in printed electronics. The obtained in-situ thermally activated ion ink can be directly coated on the surface of the substrate for sintering, thereby realizing the integrated generation and sintering of micron / nano metal particles, solving the problem that the existing metal-based conductive ink preparation process needs to first prepare micro- and nano-metal particles and then configure them into conductive ink, which has cumbersome steps, long preparation cycle and high production cost.

[0008] A method for preparing a green in-situ thermally activated ion ink comprises the following steps:

[0009] Step 1: grinding a precursor, wherein the precursor is a non-metallic single substance copper-containing precursor, silver-containing precursor, nickel-containing precursor, cobalt-containing precursor or / and gold-containing precursor;

[0010] Step 2: Mixing the ground precursor and a first solvent to prepare an in-situ thermally activated ion ink, wherein the first solvent is a reducing solvent and does not react with the precursor at room temperature.

[0011] Preferably, the copper-containing precursor is an inorganic substance containing copper ions or / and a metal organic substance containing copper ions; the silver-containing precursor is an inorganic substance containing silver ions or / and a metal organic substance containing silver ions; the nickel-containing precursor is an inorganic substance containing nickel ions or / and a metal organic substance containing nickel ions; the cobalt-containing precursor is an inorganic substance containing cobalt ions or / and a metal organic substance containing cobalt ions; the gold-containing precursor is an inorganic substance containing gold ions or / and a metal organic substance containing gold ions.

[0012] Preferably, the metal organic compound containing copper ions is one or a combination of copper acetate, copper formate, copper acetylacetonate, copper neodecanoate, copper decanoate, copper gluconate, copper citrate and copper oxalate; the metal organic compound containing silver ions is one or a combination of silver formate, silver acetate, silver citrate, silver acetylacetonate and fatty acid silver; the metal organic compound containing nickel ions is one or a combination of nickel formate, nickel acetate and nickel oxalate; the metal organic compound containing cobalt ions is cobalt acetate; the metal organic compound containing gold ions is one or a combination of gold formate and gold acetate.

[0013] Preferably, the first solvent is a combination of one or more of glycerol, ethyl acetate and polyethylene glycol.

[0014] Preferably, in step 2, the ground precursor and the first solvent are mixed to obtain a mixture, and a second solvent is added to the mixture, wherein the amount of the second solvent added does not exceed 20% of the total mass of the mixture, and the second solvent is a mixture of one or more of diethylene glycol, ethanol, ethylene glycol, and water.

[0015] Preferably, the mass ratio of the precursor to the first solvent is (0.2-1):1.

[0016] A green in-situ heat-activated ion ink is prepared by the above-mentioned preparation method.

[0017] Application of green in-situ thermally activated ion ink in printed electronics comprises the following steps:

[0018] Preparing in-situ heat-activated ion ink: preparing in-situ heat-activated ion ink by the preparation method of in-situ heat-activated ion ink;

[0019] Printing: Apply in-situ thermally activated ion ink on the substrate surface to form a conductive ink layer;

[0020] Sintering: Place it in a sintering furnace for sintering to form a conductive film on the surface of the substrate.

[0021] Preferably, the substrate surface is subjected to plasma surface treatment prior to printing.

[0022] Preferably, the sintering temperature is 120-350°C, and the sintering time is 10-120 min; the sintering atmosphere is one or a combination of air atmosphere, nitrogen atmosphere, argon atmosphere, and hydrogen atmosphere; the material of the substrate is polyimide, polyethylene terephthalate, silicon, aluminum plate, aluminum foil, copper foil, silicon carbide, gallium nitride, stainless steel or glass.

[0023] The green in-situ thermally activated ion ink and its preparation method and application proposed in the present invention do not require the preparation of micron / nano metal particles, nor do they require the introduction of resin or ethyl cellulose used in conventional ink preparation, thus avoiding organic impurities that are difficult to remove at high temperatures and greatly shortening the preparation time. The prepared in-situ thermally activated ion ink will only be activated during sintering in printed electronics applications to generate conductive metal particles, forming a conductive film with better conductive properties and better resistivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0025] Figure 1 This is a process flow chart of the preparation and application of the green in-situ thermally activated ion ink of the present invention;

[0026] Figure 2 Schematic diagram of the preparation of green in-situ thermally activated ion ink of the present invention;

[0027] Figure 3 A schematic diagram of the embossing angle between the scraper and the screen in the printing step of the present invention;

[0028] Figure 4 This is the XRD test diagram of the copper film after sintering in Example 1 of the present invention;

[0029] Figure 5 This is a SEM test image of the copper film after sintering in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present invention. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] In the present invention, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the attached drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of the present invention, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0032] In the present invention, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone.

[0033] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c" can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple.

[0034] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0035] The technical solution of the present invention is as follows:

[0036] like Figure 1 and Figure 2 As shown, the present invention provides a method for preparing a green in-situ thermally activated ion ink, comprising the following steps:

[0037] Step 1: grinding a precursor, wherein the precursor is a non-metallic single substance copper-containing precursor, silver-containing precursor, nickel-containing precursor, cobalt-containing precursor or / and gold-containing precursor;

[0038] Step 2: Mixing the ground precursor and a first solvent to prepare an in-situ thermally activated ion ink, wherein the first solvent is a reducing solvent and does not react with the precursor at room temperature.

[0039] The present invention proposes a method for preparing an in-situ heat-activated ion ink, which can be prepared by mixing at room temperature, without the need to prepare micron / nano metal particles, and without the need to introduce resin or cellulose or cellulose derivatives used in conventional ink preparation, thereby avoiding organic impurities that are difficult to remove at high temperatures and greatly shortening the preparation time. The selected first solvent must have the functions of both a solvent and a reducing agent, and the first solvent does not react with the precursor at room temperature, so that the metal particle generation and sintering can be carried out simultaneously under high-temperature heat treatment. In addition, the oxidation of easily oxidizable metal conductive ink during the preparation and storage process can be avoided, thereby avoiding the reduction of the conductivity of the conductive film. The method solves the problem that in the existing metal-based conductive ink preparation process, micro- and nano-metal particles need to be prepared first, and then configured into conductive ink, which has complicated steps, a long preparation cycle, and high production costs.

[0040] In a specific embodiment, the precursor is ground to obtain a material with a particle size of 100 nanometers to 10 micrometers.

[0041] In a specific embodiment, the copper-containing precursor is an inorganic substance containing copper ions or / and a metal organic substance containing copper ions; the silver-containing precursor is an inorganic substance containing silver ions or / and a metal organic substance containing silver ions; the nickel-containing precursor is an inorganic substance containing nickel ions or / and a metal organic substance containing nickel ions; the cobalt-containing precursor is an inorganic substance containing cobalt ions or / and a metal organic substance containing cobalt ions; the gold-containing precursor is an inorganic substance containing gold ions or / and a metal organic substance containing gold ions.

[0042] In a specific embodiment, the inorganic substance containing copper ions is one or a combination of copper oxide, cuprous oxide and copper hydroxide; the inorganic substance containing silver ions is one or a combination of silver oxide and silver carbonate; the inorganic substance containing nickel ions is one or a combination of nickel oxide, nickel hydroxide and nickel carbonate; the inorganic substance containing cobalt ions is one or a combination of cobalt hydroxide, cobalt carbonate and cobalt oxide; the inorganic substance containing gold ions is gold carbonate.

[0043] In a specific embodiment, the metal organic compound containing copper ions is one or a combination of copper acetate, copper formate, copper acetylacetonate, copper neodecanoate, copper decanoate, copper gluconate, copper citrate and copper oxalate; the metal organic compound containing silver ions is one or a combination of silver formate, silver acetate, silver citrate, silver acetylacetonate and fatty acid silver; the metal organic compound containing nickel ions is one or a combination of nickel formate, nickel acetate and nickel oxalate; the metal organic compound containing cobalt ions is cobalt acetate; the metal organic compound containing gold ions is one or a combination of gold formate and gold acetate.

[0044] In a specific embodiment, the first solvent is a combination of one or more of glycerol, ethyl acetate and polyethylene glycol. A mild reducing agent is selected, which is a green and environmentally friendly solvent to achieve green preparation, no pollution and no toxicity.

[0045] Preferably, in step 2, the ground precursor and the first solvent are mixed to obtain a mixture, and a second solvent is added to the mixture, wherein the amount of the second solvent added does not exceed 20% of the total mass of the mixture, and the second solvent can be added to adjust the viscosity according to the printing method. Preferably, the second solvent is one or a mixture of diethylene glycol, ethanol, ethylene glycol, and water.

[0046] Preferably, the mass ratio of the precursor to the first solvent is (0.2-1): 1. The above mass ratio is conducive to mixing and stirring, and can ensure film formation after coating, avoid the precursor from being unable to be completely reduced and avoid affecting the conductive performance.

[0047] The present invention also provides a green in-situ heat-activated ion ink, which is prepared by the above-mentioned preparation method.

[0048] The present invention also proposes an application of green in-situ thermally activated ion ink in printed electronics, which specifically comprises the following steps:

[0049] Preparation of in-situ heat-activated ion ink: The in-situ heat-activated ion ink is prepared by the above-mentioned preparation method of the in-situ heat-activated ion ink;

[0050] Printing: Apply in-situ thermally activated ion ink on the substrate surface to form a conductive ink layer;

[0051] Sintering: Place it in a sintering furnace for sintering to form a conductive film on the surface of the substrate.

[0052] The above application steps in printed electronics achieve the simultaneous generation and sintering of metal particles, without the need to prepare micro- and nano-metal particles, and can fundamentally avoid oxidation of easily oxidizable metal conductive inks during the preparation and storage process. The ion ink can be obtained by fully mixing the precursor and the first solvent, and the obtained in-situ thermally activated ion ink can be directly coated on the surface of the substrate for sintering, thereby achieving the integration of the generation and sintering of micron / nano metal particles, eliminating the preparation steps of micron / nano metal particles, and greatly shortening the preparation time.

[0053] Preferably, the substrate surface is subjected to plasma surface treatment before printing. During the high temperature reaction process, the substrate surface may undergo slight thermal decomposition, softening or reorganization, which may change the microstructure of the surface, forming tiny protrusions, depressions or textures, thereby increasing the surface roughness. For this reason, the substrate surface is subjected to plasma surface treatment before printing, and active groups are generated on the treated substrate surface. The first reducing solvent contains hydroxyl groups, which can increase the polarity of the substrate surface and make it easier to wet. Good wettability helps the in-situ thermally activated ion ink to spread better on the substrate surface. At the same time, high temperature accelerates the diffusion speed of the in-situ thermally activated ion ink, allowing the in-situ thermally activated ion ink to penetrate and interweave to the rough interface of the substrate. At high temperature, the thermal expansion of the substrate is also more obvious. Therefore, after cooling, the substrate shrinks and forms a strong mechanical bond with the conductive film, effectively enhancing the adhesion.

[0054] In a preferred embodiment, the sintering temperature is 120-350°C, and the sintering time is 10-120 min; the sintering atmosphere is one or a combination of air atmosphere, nitrogen atmosphere, argon atmosphere, and hydrogen atmosphere; the material of the substrate is polyimide, polyethylene terephthalate, silicon, aluminum plate, aluminum foil, copper foil, silicon carbide, gallium nitride, stainless steel or glass.

[0055] In another preferred embodiment, in the printing step, the in-situ heat-activated ion ink is coated on the substrate surface by screen printing. Figure 3 The schematic diagram of the embossing angle between the scraper and the screen is shown. Preferably, the embossing angle between the scraper and the screen is controlled at 40°-60°, which is beneficial to the uniformity and integrity of the printed layer.

[0056] Example 1

[0057] Step 1: In-situ thermal activation of ionic ink configuration

[0058] The copper acetate and copper oxide are fully ground respectively to obtain copper acetate and copper oxide with a particle size of 500 nanometers to 1 micron. The ground copper acetate and copper oxide and propylene glycol are added in sequence at a mass ratio of 1:1:3. The mixture is put into a mixer and mixed twice. Then, 5% of the total mass of diethylene glycol is added to the mixture, and the in-situ thermally activated ion ink is obtained after uniform mixing.

[0059] Step 2: Printing

[0060] 1. Clean the polyimide substrate. First, clean the substrate in an ultrasonic cleaner with deionized water for 20 minutes to remove dust and impurities on the surface of the substrate. Then, use anhydrous ethanol to perform a final cleaning for 15 minutes. After cleaning, place the substrate in a 60°C drying oven for drying. After drying, perform plasma treatment for 2 minutes. After cleaning, proceed to the next step of coating.

[0061] 2. Coating: Use screen printing to evenly coat the in-situ heat-activated ion ink on the substrate;

[0062] Step 3: Place in a rapid annealing furnace and sinter for 90 minutes at 300°C in an atmosphere of 95% argon and 5% hydrogen;

[0063] The conductive film with adhesion of ASTM 5B and resistivity of 5.6μΩ·cm was obtained. Figure 4 This is the XRD test diagram of the conductive thin film copper film after sintering; Figure 5 This is the SEM test picture of the conductive copper film after sintering.

[0064] Example 2

[0065] Step 1: In-situ thermal activation of ionic ink configuration

[0066] The copper hydroxide is fully ground to obtain copper hydroxide with a particle size of 300 nanometers to 800 nanometers, the ground copper hydroxide, polyethylene glycol 600, and glycerol are added in a mass ratio of 3:1:4 in order, the mixture is put into a mixer and mixed three times, and then 5% of the total mass of ethylene glycol is added to the mixture, and the in-situ thermally activated ion ink is obtained after uniform mixing;

[0067] Step 2: Printing

[0068] 1. Clean the glass substrate. First, clean the glass substrate in an ultrasonic cleaner with deionized water for 15 minutes to remove dust and impurities on the surface of the substrate. Then, use anhydrous ethanol to perform a final cleaning of the substrate for 5 minutes. After cleaning, place it in a 60°C drying oven for drying. After drying, perform plasma treatment for 2 minutes. After cleaning, proceed to the next step of coating.

[0069] 2. Coating: Use screen printing to evenly coat the in-situ heat-activated ion ink on the substrate;

[0070] Step 3: Place in a sintering furnace and sinter for 30 minutes at 320°C in air atmosphere;

[0071] The obtained conductive film has an adhesion of ASTM 4B and a resistivity of 13.2 μΩ·cm.

[0072] Example 3

[0073] Step 1: In-situ thermal activation of ionic ink configuration

[0074] The gold acetate is fully ground to obtain gold acetate with a particle size of 1 μm to 3 μm, the ground gold acetate powder, glycerol, diethylene glycol, and ethanol are added in a mass ratio of 3:5:1:1 in sequence, the mixture is put into a mixer and mixed twice, and the in-situ thermally activated ion ink is obtained after uniform mixing;

[0075] Step 2: Printing

[0076] 1. Clean the glass substrate to be coated. First, clean the substrate in an ultrasonic cleaner with deionized water for 15 minutes to remove dust and impurities on the surface of the substrate. Then, use anhydrous ethanol to perform a final cleaning for 15 minutes. After cleaning, put it in a drying oven for drying. After drying, perform plasma treatment for 2 minutes. After cleaning, proceed to the next step of coating;

[0077] 2. Coating: Print the in-situ heat-activated ion ink evenly on the substrate surface;

[0078] Step 3: Place in a sintering furnace and sinter for 60 minutes at 300°C in air atmosphere;

[0079] The obtained conductive film has an adhesion of ASTM 4B and a resistivity of 17.8 μΩ·cm.

[0080] Example 4

[0081] Step 1: In-situ thermal activation of ionic ink configuration

[0082] The silver carbonate is fully ground to obtain silver carbonate with a particle size of 3 microns to 10 microns, the ground silver carbonate powder, glycerol, and ethylene glycol are added in a mass ratio of 4:5:1 in sequence, the mixture is put into a mixer and mixed three times, and the in-situ thermally activated ion ink is obtained after uniform mixing;

[0083] Step 2: Printing

[0084] 1. Clean the polyimide substrate to be coated. First, clean the substrate in an ultrasonic cleaner with deionized water for 15 minutes to remove dust and impurities on the surface of the substrate. Then, use anhydrous ethanol to perform a final cleaning for 15 minutes. After cleaning, put it in a drying oven for drying. After drying, perform plasma treatment for 2 minutes. After cleaning, proceed to the next step of coating;

[0085] 2. Coating: Evenly apply the in-situ heat-activated ion ink on the substrate by screen printing;

[0086] Step 3: Place in a sintering furnace and sinter for 30 minutes at 260°C in air atmosphere;

[0087] The obtained conductive film has an adhesion of ASTM 4B and a resistivity of 26.5 μΩ·cm.

[0088] Comparative Example 1

[0089] Step 1: Preparation of Nano-Copper Particles

[0090] Comparative Example 1: In an ethylene glycol solvent, copper sulfate is reduced by hydrazine hydrate to form a copper nanoparticle suspension in the ethylene glycol solution, and nano copper particles are obtained after multiple centrifugation, washing, purification, drying, and redispersion steps, with a particle size of 100 nm to 200 nm;

[0091] Step 2: Prepare conductive ink

[0092] Dispersing copper nanoparticles in a mixed solvent of propylene glycol and ethanol to prepare nano-copper conductive ink;

[0093] Step 3: Printing

[0094] Printing nano-copper conductive ink on a polyimide substrate;

[0095] Step 4: Sintering

[0096] The nano-copper conductive ink printed on the polyimide substrate was sintered for 30 minutes under nitrogen protection at 260° C. to sinter the nano-copper conductive ink into a copper film. The resistivity of the copper film was measured to be 127.3 μΩ·cm. The adhesion of the conductive copper film on the polyimide substrate was ASTM 2B.

[0097] Compared with Comparative Example 1, Examples 1-4 of the present invention can omit the preparation steps of purifying and drying metal nanoparticles, thereby avoiding the problem of copper particle oxidation caused by the process of preparing nano-copper particles, which leads to a decrease in conductivity; at the same time, the use of toxic reagents is avoided, and the solvents and reducing agents used are all green solvents, making the preparation green and environmentally friendly.

[0098] Comparative Example 2

[0099] Step 1: Preparation of silver nanoparticles

[0100] The method of reducing silver nitrate with sodium borohydride is used to form silver nanoparticles in ethanol, and the nanosilver particles are obtained after multiple purification and drying steps, with a particle size of 50 nanometers to 100 nanometers;

[0101] Step 2: Prepare conductive ink

[0102] Nano silver particles are dispersed in a mixed solvent of ethylene glycol and ethanol, and ethyl cellulose is added to prepare a composite silver conductive ink;

[0103] Step 3: Printing

[0104] The composite silver conductive ink is coated on a polyimide substrate;

[0105] Step 4: Sintering

[0106] The composite silver conductive ink coated on the polyimide substrate was sintered for 30 min in an air atmosphere at 240°C to obtain a silver film;

[0107] The adhesion of the silver film formed after sintering to the polyimide substrate was tested to be ASTM 4B, and the resistivity of the silver film was 87.7 μΩ·cm.

[0108] Comparative Example 3

[0109] Step 1: Ion ink preparation

[0110] The copper acetate and copper oxide are fully ground respectively to obtain copper acetate and copper oxide with a particle size of 500 nanometers to 1 micron. The ground copper acetate and copper oxide and propylene glycol are added in sequence at a mass ratio of 0.1:1. The mixture is put into a mixer and mixed twice. Then, 5% of the total mass of diethylene glycol is added to the mixture, and the ion ink is obtained after uniform mixing.

[0111] Step 2: Printing

[0112] 1. Clean the polyimide substrate. First, clean the substrate in an ultrasonic cleaner with deionized water for 20 minutes to remove dust and impurities on the surface of the substrate. Then, use anhydrous ethanol to perform a final cleaning for 15 minutes. After cleaning, place the substrate in a 60°C drying oven for drying. After drying, perform plasma treatment for 2 minutes. After cleaning, proceed to the next step of coating.

[0113] 2. Coating: Use screen printing to evenly coat the ion ink on the substrate;

[0114] Step 3: Place in a rapid annealing furnace and sinter for 90 minutes at 300°C in an atmosphere of 95% argon and 5% hydrogen;

[0115] The obtained conductive film has an adhesion of ASTM2B and a resistivity of 175.9 μΩ·cm.

[0116] Comparative Example 4

[0117] Step 1: Ion ink preparation

[0118] The copper acetate and copper oxide are fully ground respectively to obtain copper acetate and copper oxide with a particle size of 500 nanometers to 1 micron. The ground copper acetate and copper oxide and propylene glycol are added in sequence at a mass ratio of 1.5:1. The mixture is put into a mixer and mixed twice. Then, 5% of the total mass of diethylene glycol is added to the mixture, and the ion ink is obtained after uniform mixing.

[0119] Step 2: Printing

[0120] 1. Clean the polyimide substrate. First, clean the substrate in an ultrasonic cleaner with deionized water for 20 minutes to remove dust and impurities on the surface of the substrate. Then, use anhydrous ethanol to perform a final cleaning for 15 minutes. After cleaning, place the substrate in a 60°C drying oven for drying. After drying, perform plasma treatment for 2 minutes. After cleaning, proceed to the next step of coating.

[0121] 2. Coating: Use screen printing to evenly coat the ion ink on the substrate;

[0122] Step 3: Place in a rapid annealing furnace and sinter for 90 minutes at 300°C in an atmosphere of 95% argon and 5% hydrogen;

[0123] The obtained conductive film has an adhesion of ASTM3B and a resistivity of 56.3 μΩ·cm.

[0124] Comparison table of test data of embodiment and comparative example

[0125] Group Adhesion (ASTM) Resistivity (μΩ·cm) Contaminated / toxic reagents used Example 1 5B 5.6 none Example 2 4B 13.2 none Example 3 4B 17.8 none Example 4 4B 26.5 none Comparative Example 1 2B 127.3 Hydrazine hydrate Comparative Example 2 4B 87.7 Sodium borohydride Comparative Example 3 2B 175.9 none Comparative Example 4 3B 56.3 none

[0126] It can be seen from the above embodiments and comparative examples that the ionic ink obtained by the preparation process and proportions proposed in the present invention can achieve or even exceed the effect of conventional metal conductive inks, and has a good use effect; while simplifying the preparation process, it is green and environmentally friendly, which is conducive to industrial production.

Claims

1. A method for preparing a green in-situ thermally activated ion ink, characterized in that: The following steps are involved: Step 1: grinding a precursor, wherein the precursor is a non-metallic single substance copper-containing precursor, silver-containing precursor, nickel-containing precursor, cobalt-containing precursor or / and gold-containing precursor; Step 2: Mixing the ground precursor and a first solvent to prepare an in-situ thermally activated ion ink, wherein the first solvent is a reducing solvent and does not react with the precursor at room temperature.

2. The method for preparing the green in-situ thermally activated ion ink according to claim 1, characterized in that: The copper-containing precursor is an inorganic substance containing copper ions or / and a metal organic substance containing copper ions; the silver-containing precursor is an inorganic substance containing silver ions or / and a metal organic substance containing silver ions; the nickel-containing precursor is an inorganic substance containing nickel ions or / and a metal organic substance containing nickel ions; the cobalt-containing precursor is an inorganic substance containing cobalt ions or / and a metal organic substance containing cobalt ions; the gold-containing precursor is an inorganic substance containing gold ions or / and a metal organic substance containing gold ions.

3. The method for preparing the green in-situ thermally activated ion ink according to claim 2, characterized in that: The copper ion-containing metal organic compound is one or a combination of copper acetate, copper formate, copper acetylacetonate, copper neodecanoate, copper decanoate, copper gluconate, copper citrate and copper oxalate; the silver ion-containing metal organic compound is one or a combination of silver formate, silver acetate, silver citrate, silver acetylacetonate and fatty acid silver; the nickel ion-containing metal organic compound is one or a combination of nickel formate, nickel acetate and nickel oxalate; the cobalt ion-containing metal organic compound is cobalt acetate; the gold ion-containing metal organic compound is one or a combination of gold formate and gold acetate.

4. The method for preparing the green in-situ thermally activated ion ink according to claim 1, characterized in that: The first solvent is a combination of one or more of glycerol, ethyl acetate and polyethylene glycol.

5. The method for preparing the green in-situ thermally activated ion ink according to claim 1, characterized in that: In step 2, the ground precursor and the first solvent are mixed to obtain a mixture, and a second solvent is added to the mixture. The amount of the second solvent added does not exceed 20% of the total mass of the mixture. The second solvent is one or a mixture of diethylene glycol, ethanol, ethylene glycol, and water.

6. The method for preparing the green in-situ thermally activated ion ink according to claim 1, characterized in that: The mass ratio of the precursor to the first solvent is (0.2-1):

1.

7. A green in-situ thermally activated ion ink, characterized in that: The ionic ink is prepared by the preparation method described in any one of claims 1 to 6.

8. Application of green in-situ thermally activated ion ink in printed electronics, characterized in that: The following steps are involved: Preparation of in-situ heat-activated ion ink: preparing in-situ heat-activated ion ink by the preparation method of green in-situ heat-activated ion ink according to any one of claims 1 to 7; Printing: Apply in-situ thermally activated ion ink on the substrate surface to form a conductive ink layer; Sintering: Place it in a sintering furnace for sintering to form a conductive film on the surface of the substrate.

9. The use of the green in-situ thermally activated ion ink in printed electronics according to claim 8, characterized in that: The substrate surface was plasma treated before printing.

10. The use of the green in-situ thermally activated ion ink in printed electronics according to claim 8, characterized in that: The sintering temperature is 120-350°C, and the sintering time is 10-120 minutes; the sintering atmosphere is one or a combination of air atmosphere, nitrogen atmosphere, argon atmosphere, and hydrogen atmosphere; the material of the substrate is polyimide, polyethylene terephthalate, silicon, aluminum plate, aluminum foil, copper foil, silicon carbide, gallium nitride, stainless steel or glass.

Citation Information

Patent Citations

  • In-situ nano-copper paste and preparation process and application thereof

    CN111906325A

  • Ultra-short pulse laser direct writing method for flexible humidity sensor

    CN116425106A

  • Preparation method and application of conductive ink

    CN118994970A